University Outdoor Activities: an integral approach in the professional formation - María Ofelia Armas-Álvarez (Podium, 2012)
The work is lead to establish the theoretical foundations of the university outdoor labour from the organizational forms of the teaching process that favour the knowledge acquisition and the development of necessary skills in the students to promote culture in the different moments where they have connection with the society by means of the participation of the subjects and disciplines of the current programs that allow to organize systematic and articulated activities, appropriately planned, able to satisfy the necessities and to achieve the purpose of getting the preparation and integral cultural formation, as well as the their appropriate projection in the social environment that demands the contemporary society from the university professionals. In the work they are determined the content and skills that the student requires to promote Physical Culture in correspondence with their professional performance. It is designed a plan of activities to carry out the university outdoor labour from the organizational forms of the teaching process.